2014
DOI: 10.1021/ja508461m
|View full text |Cite
|
Sign up to set email alerts
|

Flipping in the Pore: Discovery of Dual Inhibitors That Bind in Different Orientations to the Wild-Type versus the Amantadine-Resistant S31N Mutant of the Influenza A Virus M2 Proton Channel

Abstract: Influenza virus infections lead to numerous deaths and millions of hospitalizations each year. One challenge facing anti-influenza drug development is the heterogeneity of the circulating influenza viruses, which comprise several strains with variable susceptibility to antiviral drugs. For example, the wild-type (WT) influenza A viruses, such as the seasonal H1N1, tend to be sensitive to antiviral drugs, amantadine and rimantadine, while the S31N mutant viruses, such as the pandemic 2009 H1N1 (H1N1pdm09) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
115
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 82 publications
(120 citation statements)
references
References 68 publications
4
115
0
1
Order By: Relevance
“…Structures determined using X-ray crystallography, solution NMR, and solid-state NMR (SSNMR) support this acid-activated transporter-like mechanism (9,10,(18)(19)(20)(21)(22)(23)(24)(25)(26). Near neutral pH the channel is closed in the C closed conformation ( Fig.…”
Section: Significancementioning
confidence: 77%
“…Structures determined using X-ray crystallography, solution NMR, and solid-state NMR (SSNMR) support this acid-activated transporter-like mechanism (9,10,(18)(19)(20)(21)(22)(23)(24)(25)(26). Near neutral pH the channel is closed in the C closed conformation ( Fig.…”
Section: Significancementioning
confidence: 77%
“…However, recent functional and structural studies lend further support to lumenal adamantane binding, including those on chimeric influenza A/influenza B M2, where the lumenal domain originates from the drug-sensitive IAV M2 and the peripheral domain from the resistant BM2 Pielak et al, 2011). Adamantanes bound to the lumen in all cases where inhibition occurred and lumenal binding has also been documented for novel adamantane derivatives shown to inhibit amantadine-resistant Ser31Asn mutant M2 channels (Wang et al, 2013a, c;Williams et al, 2013;Wu et al, 2014).…”
Section: Iav M2mentioning
confidence: 90%
“…The majority of novel inhibitors identified to date involve either derivatization of amantadine or another M2-inhibitory compound, BL-1743, which was identified from a yeast-based M2 screen (Duque et al, 2011;Kurtz et al, 1995;Rey-Carrizo et al, 2013, 2014Tu et al, 1996;Wang et al, 2009Wang et al, , 2011aWang et al, , b, 2013aWu et al, 2014). Effective inhibitors of several drug-resistant variants have been identified by this approach, although far fewer hits capable of blocking Asn31 channels have arisen.…”
Section: Iav M2mentioning
confidence: 99%
“…In addition, positively charged fragment-like molecules, such as amantadine (44) and 2-guanidinobenzimidazole (2GBI) (30), are known to act as pore blockers of M2 and Hv1, respectively. Many groups, including ours, have successfully pursued drug discovery projects with M2 as a target (45)(46)(47)(48)(49)(50)(51)(52)(53). In particular, we have recently shown that scaffold replacement of hydrogen-bonded Significance Hv1, a voltage-gated proton channel, is an emerging pharmacological target implicated in many pathological conditions, including cancer and ischemic brain damage.…”
mentioning
confidence: 99%